THE USAGE OF MULTIPLE CHOICE AND GAP FILLING IN MEASURING GRADE-SCHOOLERS’ UNDERSTANDING OF GRAMMAR - Astri Yuniar Sri Utari (Eltin Journal : Journal of English Language Teaching in Indonesia, 2013)
Grammar is one of the important elements in English that must be mastered or at least   understood by the learners. In measuring students’ understanding of grammar, teachers can use four kinds of tests. They are gap filling, paraphrase, completion, and multiple choice. Multiple choice and gap filling are commonly used in assessing grade-schoolers’ understanding of grammar. Both of them are considered easy tests. Thus, there shouldt be no difference in students’ scores, whether using multiple choice test or gap filling test. This study is conducted to find a brief comparison  of the usage of multiple choice and  gap  filling in measuring their understanding of grammar. This study also tries to determine which test is more influential in measuring the students’ understanding of grammar. This study uses quantitative approach. The data collection is obtained from students’ scores in both tests and the questionnaires. Through data analysis it is found that there is a significant difference in students’ scores of multiple choice and gap filling test. Students’ multiple choice scores are significantly better than their gap filling scores. It is also found that most of students believe that  gap  filling  test  is  better  than  multiple  choice  test  to  assess  their understanding of grammar. KEYWORDS:  grammar,  multiple  choice  test,  gap  filling  test,  paraphrase, completion